Application of Light Expanded Clay Aggregate as Replacement of Coarse Aggregate in Concrete Pavement - A, Pavithra; De Rose D, Jerosia (International Journal of Engineering and Technology, 2018)
The main aim of this project is to develop a light weight concrete (LWC) by replacing the coarse aggregate with light weight expanded clay aggregate. The damage caused in LWC is less significant than conventional concrete and therefore the maintenance cost is also reduced. In order to understand the effect of light weight aggregate in concrete, conventional concrete of strength 30MPa was designed with the density of 2400 kg/m3. Then the natural coarse aggregates were replaced by clay aggregates and light weight concrete mix of density 1800 kg/m3 was designed to meet the desired strength requirement. As the density of the concrete tends to be lowered, the strength of the concrete may also tend to decrease. Hence suitable chemical and mineral admixture is to be incorporated in addition to significant water reduction to meet the strength requirement. Cement content kept constant in both the cases. The details of mechanical properties and durability properties of conventional and light weight concrete are reported in this paper.Â